Kajian Nilai Tukar Sanksi Hukum Pidana Adat Dayak sebagai Pedoman bagi Temenggung di Kabupaten Sintang - Salim, Kartika Agus (Proceedings Series on Social Sciences & Humanities, 2025)
Customary law communities are social communities of people who feel united because they are bound by common ancestors and or certain areas, inhabit certain areas, have their own wealth, are led by one or several people who have authority and power and have a system of values as a guideline for life and have no desire to separate themselves. 1 In resolving cases in Kutai, and also functions as a standard of exchange; the value of 1 antakng is equivalent to Rp. 400,000; 2. The Dayak community in Sintang Regency if they pay the customary sanctions decided by the Temenggung by handing over traditional items such as Gong (Kolatung/solokanong), Tempayan (Bolang’ak, Potoran), Kujur (Lunjuk), Bracelet (Sambon, manas) to the victim. However, these items are currently difficult to find so they are converted into money with different values, for example 1 Jihpon is calculated with Rp. 500,000 (Five Hundred Thousand Rupiah) or 1 (one) Gantang of Rice, or 1 tael is calculated with Rp. 50,000 (Fifty Thousand Rupiah). The legal issue lies in the equivalence of the monetary value for each Dayak Sub-Tribe, which has not yet been determined to adjust the nominal fine category in the Criminal Code Category II. If customary criminal law is implemented, how will judges or the village head determine the customary fines, which differ between sub-tribes? Therefore, a consensus is needed to guide the village head in customary courts. Furthermore, is the Category II fine acceptable to the customary law community?